Prevalence of chronic diabetic complications and associated risk factors among follow-up diabetic patients: estimates from a referral national diabetes center in Yemen - Gamil Ghaleb Alrubaiee (BMC Endocrine Disorders)
Abstract Background Emergence and progression of diabetic complications are associated with several risk factors. Identifying these risk factors related to diabetes helps avoid such complications and develop preventive measures to protect patients and improve their quality of life. This study aimed to estimate the prevalence of chronic complications among Yemeni diabetic patients and investigate the associations between these complications, sociodemographic characteristics, and diabetic risk factors. Methods This cross-sectional study was conducted at the National Diabetic Referral Center in Sana’a, Yemen, from September 1 to October 30, 2023. Of the 228 respondents, 222 were considered valid for analysis. Data for this study were collected using the World Health Organization (WHO) STEPS Surveillance questionnaire and a simple physical assessment. IBM SPSS version 24.0 was utilized to manage and analyze the data. Descriptive statistics were used to determine the prevalence of diabetes complications. The chi-square test and binary logistic regression were used to determine the associations and risk factors. A p-value of less than 0.05 was used to determine statistical significance. Results Diabetes-related complications were reported by 62.6% of respondents, with females having a greater risk of diabetic foot, nephropathy, and retinopathy, while males had an increased risk of neuropathy complications. Unemployment, obesity, non-adherence to diabetes regimens, uncontrolled hypertension, longer duration of type 1 diabetes (T1DM), and irregular physician check-ups were identified as key predictors of diabetes-related complications. Administration of statins as lipid-lowering medications was associated with a reduced risk of coronary artery disease (CAD) or ischemic stroke complications. Conclusion Chronic complications related to diabetes were common among patients in Yemen. Factors such as unemployment, obesity, non-adherence to diabetes regimens, uncontrolled hypertension, longer duration of T1DM, and irregular physician check-ups were identified as key predictors of these complications. Implementation of the WHO non-communicable disease package is strongly recommended. This package comprises comprehensive measures aimed at detecting, treating, preventing, and controlling diabetic complications and ultimately improving the overall management of diabetes in Yemen. Clinical trial number Not applicable.